Internet usage among undergraduate dental students in India - Kumar, Santhosh (2010)
Purpose: To assess the internet usage among dental students at a private dental institution in India. Methods: Internet usage was assessed among the first- to senior-year undergraduate dental students at the Darshan Dental College and Hospital, Udaipur, India. The study was conducted during the beginning of the academic year 2007-2008. Data were collected by using a questionnaire, which consisted of nine multiple choice questions. The chi-square test was used to compare the responses between male and female students and to analyze the difference among year classes. Results: The total sample size was 247, and the overall response rate was 66%. Only 5.7% and 4.1% of the students used the internet daily for general and dental purposes, respectively. More than half the subjects (55.5%) never used the internet for academic purposes in comparison to 9.3% for general use. Nearly half of the subjects preferred home for internet access; only 7.9% accessed the internet at school. About 60% of the subjects used search engines to access dental subjects, and the students from clinical years used the search engines for dental education more often than the preclinical students (78% versus 41.2%, P=0.001). Conclusion: Dental students at this private dental institution in India reported lower levels of internet use than students in other countries, which may be due to limited access and availability at the present institution.